2018
DOI: 10.3390/rs10010056
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of BRDF, NDVI and Wind Speed to the Aerodynamic Roughness Length over Sparse Tamarix in the Downstream Heihe River Basin

Abstract: Abstract:The aerodynamic roughness length (z0m) is an important parameter that affects the momentum and energy exchange between the earth surface's and the atmosphere. In this paper, the gradient wind speed data that were observed from May to October, 2014, at the Si Daoqiao station, which is located in an area of sparse Tamarix in the downstream region of the Heihe River Basin (HRB), are used to evaluate the sensitivity of the moderate-resolution imaging spectroradiometer (MODIS) near-infrared (NIR) bi-direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Satellite remote sensing provides the ability to produce area-weighted or integrated estimates of land surface characteristics across pixels (e.g., 500 × 500 m). Approaches tested to resolve areal z 0 and u s* include radar backscatter coefficients (Greeley et al, 1991(Greeley et al, , 1997Marticorena et al, 2004Marticorena et al, , 2006, surface shadowing (Chappell et al, 2010;Chappell & Heritage, 2007;Cho et al, 2012), and sensor bidirectional reflectance distribution function (BRDF) parameters (Xing et al, 2018). Using data from wind tunnel experiments, Chappell and Webb (2016) showed that aerodynamic sheltering can be approximated from land surface albedo normalized to remove surface spectral effects.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite remote sensing provides the ability to produce area-weighted or integrated estimates of land surface characteristics across pixels (e.g., 500 × 500 m). Approaches tested to resolve areal z 0 and u s* include radar backscatter coefficients (Greeley et al, 1991(Greeley et al, , 1997Marticorena et al, 2004Marticorena et al, , 2006, surface shadowing (Chappell et al, 2010;Chappell & Heritage, 2007;Cho et al, 2012), and sensor bidirectional reflectance distribution function (BRDF) parameters (Xing et al, 2018). Using data from wind tunnel experiments, Chappell and Webb (2016) showed that aerodynamic sheltering can be approximated from land surface albedo normalized to remove surface spectral effects.…”
Section: Introductionmentioning
confidence: 99%